Factors Associated with Acute Complications among Individuals with Type 1 Diabetes in China: The 3C Study. (2nd January 2020) - Liu, Wei; McGuire, Helen C.; Kissimova-Skarbek, Katarzyna; Zhou, Xianghai; Han, Xueyao; Wang, Yanai; Jaacks, Lindsay M.; Zhang, Simin; Lin, Shaoda; Ji, Linong
ABSTRACT: Background : To identify the sociodemographic and clinical characteristics related to the occurrence of diabetic ketoacidosis (DKA) and frequent hypoglycemia in children, adolescents and adults with type 1 diabetes in China. Methods : The 3C Study was an epidemiological study that recruited 849 type 1 diabetes patients aged 0–78 years in Beijing and Shantou, China. Separate logistic regression models were used to evaluate the association of sociodemographic and clinical factors with the occurrence of DKA in the past 12 months or frequent hypoglycemia (≥5 episodes) in the past 7 days. Results : Children and adolescents were significantly more likely to have DKA in the past 12 months compared to adults: odds ratio (OR) and (95% confidence interval [CI]), 4.67 (1.90, 11.52) for <13 years and 4.00 (1.59, 10.10) for 13 to <19 years. Underweight participants were also more likely to have DKA relative to normal weight participants: OR (95% CI), 6.87 (2.64, 17.87). Children and participants who did not receive diabetes education in the past 12 months were more likely to have frequent hypoglycemia: OR (95% CI), 2.95 (1.23, 7.06) and 7.67 (1.77, 13.2), respectively. Participants who reported self-monitoring of blood glucose ≤2 times/week (ref: 7 times/week) and participants who had higher HbA1c levels were less likely to have frequent hypoglycemia: OR (95% CI), 0.14 (0.03, 0.64) and 0.78 (0.63, 0.96), respectively. Gender, family income, parent education, health insurance coverage, diabetes duration, and insulin administration method were not significantly associated with DKA or frequent hypoglycemia in this sample. Conclusions : Children, adolescents and underweight individuals with type 1 diabetes in China were more likely to report DKA, and children, individuals without adequate diabetes education, and those with lower HbA1c levels were more likely to have frequent hypoglycemia. These patients should be targeted for preventive interventions.